Systematic Review and Meta-analysis of Endoscopic vs Microscopic Stapes Surgery for Stapes Fixation. (November 2021) - Ho, Sandra; Patel, Prayag; Ballard, Daniel; Rosenfeld, Richard; Chandrasekhar, Sujana
Objective: To systematically review the current literature regarding the operative outcomes of stapes surgery for stapes fixation via the endoscopic and microscopic approaches. Data Sources: PubMed, Embase, and Web of Science. Review Methods: An electronic search was conducted with the keywords "endoscop* or microscop*" and "stapes surgery or stapedectomy or stapedotomy or otosclerosis or stapes fixation." Studies were included if they compared endoscopy with microscopy for stapes surgery performed for stapes fixation and evaluated hearing outcomes and postoperative complications. Articles focusing on stapes surgery other than for stapes fixation were excluded. Results: The database search yielded 1317 studies; 12 remained after dual-investigator screening for quantitative analysis. The mean MINORS score was 18 of 24, indicating a low risk of bias. A meta-analysis demonstrated no statistically significant difference between the groups with regard to operative time, chorda tympani nerve manipulation or sacrifice, or postoperative vertigo. There was a 2.6-dB mean improvement in the change in air-bone gap in favor of endoscopic stapes surgery and a 15.2% increased incidence in postoperative dysgeusia in the microscopic group, but the studies are heterogeneous. Conclusions: Endoscopic stapes surgery appears to be a reasonable alternative to microscopic stapes surgery, with similar operative times, complications, and hearing outcomes. Superior visibility with the endoscope was consistently reported in all the studies. Future studies should have standardized methods of reporting visibility, hearing outcomes, and postoperative complications to truly establish if endoscopic stapes surgery is equivalent or superior to microscopic stapes surgery.